1.b^2+4a(b+a)2.9x^2y+y^3-6xy^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 17:27:16
1.b^2+4a(b+a)2.9x^2y+y^3-6xy^21.b^2+4a(b+a)2.9x^2y+y^3-6xy^21.b^2+4a(b+a)2.9x^2y+y^3-6xy^21.原式=b^2+4
1.b^2+4a(b+a)2.9x^2y+y^3-6xy^2
1.b^2+4a(b+a)
2.9x^2y+y^3-6xy^2
1.b^2+4a(b+a)2.9x^2y+y^3-6xy^2
1.原式=b^2+4ab+4a^2
=(b+2a)^2
2.原式=y(9x^2+y^2-6xy)
=y[(3x)^2-6xy+y^2}
=y(3x-y)^2
①(b+2a)^2
②y(3x-y)^2
1.b^2+4a(b+a)2.9x^2y+y^3-6xy^2
(x+y)(a-2b)
2x(a-b)-4y(b-a )因式分解
(2a-b)(4a²+b²)(b+a) (2x-y)²-4(x-y)(x+2y)
(2a+b)(2a-3b)+3a(2a+b)和x(x+y)(x-y)-x(x+y)²4a(x+y)-6x-6y和啊a(a-b)-ab+b²
因式分解:x^2y^2-4x a(a-b)-2b(b-a)
因式分解:a(x-y)^2+b(y-x)^3 4(x-y)^2+8(y-x)(x+y)1.a(x-y)^2+b(y-x)^3 2.4(x-y)^2+8(y-x)(x+y)
x(x-1)-(x^2-y)=-3.求x^2+y^2-2xy的值.[(2a+b)(2a-b)-(2a-b)^2+2b(a-b)]/4b,其中a=2,b=1.
计算 1.[(a+b)^2-(a+b)(a-b)]÷(-b) 2.[(x+y)(2x+y)+(x+y)(x-y)]÷3x
1.x(x-y)+y(y-x)2.9(a-b)^2-16(a+b)^2 3.25(x-y)^2+10(y-x)+1
因式分解:4a(x-y)-2b(x-y)
4a(x-y)-2b(y-x)
4a(x-y)-2b(y-x)
(3x^/4y)^*2y/3y+x^2y^÷2y^/x 还有一个 (a+b/a-b)^*(2a-2b/3a+3b)-a^/a^-b^÷a/b
通分 a/(y-x)^2,b/(x-y)(x+y)
因式分解a(x-y)+b(y-x)+(2x-y)
1.x(x-y)-(x-3)(x+3) 2.(a^2+b^2)(a+b)(a-b) 3.(a-2b+3c)(a+2b-3c) 4.(x+y-z)(x-y+z) 5.(x^8+y^8)(x^4+y^4)(x^2+y^2)(x+y)(x-y)
4a^2x-4a^2y-b^2x+b^y如题